THE IMPACT OF EDUCATIONAL CONTENT TOWARD AUDIENCE PERCEPTIONS ON INSTAGRAM (Case Study @naturelovingeduhub) - Eryc Eryc (Sean Institute, 2022)
The development of information and communication technology provides demand in lifestyle of users. Nowadays everyone could access the internet easily and interact with everybody in various social media sites. Social media could not only be used as a communication tool, but also has many functions for the community, one of which can be used as a medium to present educational content. In this study an analysis of the types of educational content uploaded by one Instagram account @naturelovingeduhub through their Instagram platform in their efforts to influence their audience to participate in movements to sustainability environmental problems and to get a clear understanding of their audiences’ perceptions and thoughts on educational content. The purpose of this research is further divided into two points, to identify the different categories of educational content created by @naturelovingeduhub on Instagram and to determine the audience's perception of the educational content posted. This study uses a qualitative approach, which is the data will be obtained through analysis of content on posts on Instagram in the past year and conducting interviews with selected respondents to determine respondents' perceptions after long exposure to educational content provided by the account.